TINGKAT MOTIVASI DAN PERCAYA DIRI SISWA DALAM PEMBELAJARAN PENDIDIKAN JASMANI PADA SISWA KELAS IV SDN 1 KANDANGAN KOTA - Muhammad Robby Franata; Akhmad Amirudin; Nurdiansyah; Januar Inggar Yadi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the level of motivation and self-confidence among fourth-grade students at SDN 1 Kandangan Kota in participating in physical education classes. Using a survey methodology, this study employed quantitative descriptive techniques. A total of 43 Year IV pupils from Classes A and B formed the sample for this study. The research tools utilised in this study were reliability and validity tests for the motivation and self-confidence surveys. Percentages were used in the data analysis. The pupils’ levels of motivation and self-confidence were found to be quite high (83% and 75% respectively) based on the study’s findings. The majority of the children demonstrated high levels of enthusiasm, curiosity, courage and engagement in sport, both inside and outside the classroom, according to the study’s findings. Teachers and schools can use this research as a benchmark to assess how effectively they are improving physical education classes through enjoyable and creative lessons.